Regulation of the hexaheme nitrite/nitric oxide reductase of Desulfovibrio desulfuricans, Wolinella succinogenes and Escherichia coli. A mass spectrometric study - Costa, C. (2019)
Dissimilatory nitrite reduction, carried out by hexaheme proteins, gives ammonia as the final product. Representatives of this enzyme group from 3 bacterial species can also reduce NO to either ammonia or N2O. The redox regulation of the nitrite/nitric oxide activities is discussed in the context of the denitrifying pathway.